HUBUNGAN KEMATANGAN KARIR DAN SELF REGULATED LEARNING DENGAN KECURANGAN AKADEMIK PADA MAHASISWA : Penelitian Korelasional pada Mahasiswa Fakultas Ilmu Pendidikan Universitas Pendidikan Indonesia - Prativi, Asti (2017)
Penelitian ini bertujuan untuk mengetahui hubungan antara kematangan karir dan self regulated learning dengan kecurangan akademik pada mahasiswa Fakultas Ilmu Pendidikan UPI. Pendekatan yang digunakan adalah pendekatan kuantitatif dengan analisis korelasional. Sampel dalam penelitian ini berjumlah 329 mahasiswa Fakultas Ilmu Pendidikan UPI. Instrumen pada penelitian ini adalah Career Adapt-Abilities Scales (CAAS), Motivated Strategies for Learning-Questionnaire (MSLQ), dan Skala Kecurangan Akademik. Hasil yang diperoleh menunjukkan bahwa (1) terdapat hubungan negatif yang signifikan antara kematangan karir dengan kecurangan akademik, (2) terdapat hubungan negatif yang signifikan antara self regulated learning dengan kecurangan akademik, dan (3) terdapat hubungan yang signifikan antara kematangan karir dan self regulated learning dengan kecurangan akademik pada mahasiswa Fakultas Ilmu Pendidikan UPI dimana kematangan karir dan self regulated learning dapat memprediksi kecurangan akademik sebesar 26,5%. ;---This research aims to investigate the relationship between career maturity and self regulated learning with academic cheating in the Faculty of Education Science students at Indonesia University of Education. The approach used is quantitative approach with correlational analysis. The sample in this research amounted to 329 students of the Faculty of Education Science at Indonesia University of Education. The instruments of this research are Career Adapt-Abilities Scales (CAAS), Motivated Strategies for Learning-Questionnaire (MSLQ), and Academic Cheating Scale. The results obtained show that; (1) there is a significant negative relationship between career maturity with academic cheating, (2) there is a significant negative relationship between self regulated learning with academic cheating, (3) there is a significant relationship between career maturity and self regulated learning with academic cheating in the Faculty of Education Science students at Indonesia University of Education where the career maturity and self regulated learning can predict the academic cheating as much as 26,5%.